2000
DOI: 10.1002/1098-2396(20001201)38:3<355::aid-syn15>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and short-term lithium administration on dialysate glutamate and GABA levels in the frontal cortex of the conscious rat

Abstract: In the present study, we employed in vivo microdialysis in the frontal cortex of the awake rat to investigate the effects of acute and short‐term (twice daily, 3 days) lithium chloride administration (1, 2, and 4 meq/kg, s.c.) on local dialysate glutamate and GABA levels. Acute lithium (1 meq/kg) failed to influence cortical glutamate levels while the higher (2 and 4 meq/kg) doses increased (+38 ± 6% of basal levels) and reduced (‐27 ± 4%) cortical glutamate levels, respectively. Cortical GABA levels were affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…This result is consistent with several studies showing lithium to induce an acute and subacute increase of GABA in the rat brain. [63][64][65] GABA receptor binding has also previously been found to be decreased in rat brain after chronic lithium treatment, indicating a downregulation of GABA receptors, potentially through overactivation of the system. 66 This is the first report of an increase in GABA levels after chronic lithium treatment.…”
Section: Post-mortem Brain Tissue Analysismentioning
confidence: 85%
“…This result is consistent with several studies showing lithium to induce an acute and subacute increase of GABA in the rat brain. [63][64][65] GABA receptor binding has also previously been found to be decreased in rat brain after chronic lithium treatment, indicating a downregulation of GABA receptors, potentially through overactivation of the system. 66 This is the first report of an increase in GABA levels after chronic lithium treatment.…”
Section: Post-mortem Brain Tissue Analysismentioning
confidence: 85%
“…71 Conversely, another recent study in rats found that lower doses of lithium led to increases in cortical glutamate concentration. 72 Notably, it is also an established clinical fact that lithium levels required for an acute antimanic response (that is, > 0.9 mmol l À1 ) exceed those required for relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically diverse effects of lithium on the glutamateric system have been identified by a number of groups (Antonelli et al, 2000;Dixon and Hokin, 1998;Dixon et al, 1994;Du et al, 2004;Du et al, 2006;Gray et al, 2003;Hokin et al, 1996;Marcus et al, 1986). Specifically, these effects include evidence suggesting a decrease in glutamate reuptake, decrease in glutamate release, and/or modulation of receptor levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many biochemical effects of lithium, evidence has suggested actions on the glutamateric system (Antonelli et al, 2000;Dixon and Hokin, 1998;Dixon et al, 1994;Du et al, 2004;Hokin et al, 1996;Marcus et al, 1986). A substantial body of data suggests that the AMPA receptor subclass of glutamate receptors may be particularly interesting targets for the treatment of mood disorders (Alt et al, 2006;Li et al, 2001;Li et al, 2003;Martinez-Turrillas et al, 2002; Svenningsson et al, 2002).…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation